Innovative strategies for teaching English in special school: Teachers’ experiences and voices - Faiza, Nurul; Astutik, Yuli (Journal of Research on English and Language Learning (J-REaLL), 2025)
Teaching English to students with special needs is certainly not an easy way. So, teachers need to use teaching methods that best suit their students’ conditions. Therefore, this research aims to explore how teachers design English teaching methods and their implementation. Apart from that, this research also describes the challenges faced by English teachers in special schools (SLB). This research was conducted at SLB-AC Dharma Wanita Sidoarjo Regency. The participants in this research were English teachers at junior high schools. This qualitative research uses interview and observation data collection techniques. The results of this research show that teachers use various methods adapted to students’ ability levels, including severe, mild, and special classes, according to their needs. The methods applied reflect awareness of the importance of individualization to support special needs students in learning English. Challenges faced by teachers, such as grouping students based on ability, handling students’ moods, and preparing appropriate learning materials, were also issues found in this research. The results of this research imply that teachers must understand that each student has special needs.